A anamorfose na composição de Las meninas de Picasso - Nascimento, Geraldo Carlos do (2000)
The reading that Picasso has done of Velázquez’s portrait Las meninas demonstrates evidences of a process of distortions which is shown on the fifty-eight canvases that he had painted inspired in the abovementioned masterpiece. This text intends to mark that those distortions, which - according to Jacques Lacan - are typical from an anamorphics process, went deeper as Picasso moved away from the original and allowed his own enunciation to come out.